2020
DOI: 10.21273/horttech04639-20
|View full text |Cite
|
Sign up to set email alerts
|

A Sensory Analysis of Raw Native, ‘Kanza’, and ‘Pawnee’ Pecans

Abstract: The purpose of this study is to evaluate the appearance, texture, color, and taste of two popular pecan (Carya illinoinensis) clones relative to native pecans in a blind sensory analysis. Subjects tasted the raw pecans acquired from the same farm and evaluated them using hedonic scores. Results suggest consumers prefer the two clones to natives, and most of this preference seems to be related to the pecan size. A crossmodal effect was detected whereby the subjects reported an improved flavor in whole native pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The findings implied that the selected pecan varieties generally had good sensory qualities. The results were consistent with a study that showed high hedonic ratings toward three pecan varieties (Kanza, Pawnee, and two natives) for the acceptance of appearance, texture, flavor, and overall [ 6 ]. The study also concluded that pecan kernel size was the major factor impacting consumer preference, which was contrary to our results.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The findings implied that the selected pecan varieties generally had good sensory qualities. The results were consistent with a study that showed high hedonic ratings toward three pecan varieties (Kanza, Pawnee, and two natives) for the acceptance of appearance, texture, flavor, and overall [ 6 ]. The study also concluded that pecan kernel size was the major factor impacting consumer preference, which was contrary to our results.…”
Section: Discussionsupporting
confidence: 91%
“…In this study, PLS regression showed that the drivers of overall acceptance were the acceptance of typical-pecan flavor and interior color, intensities of flavors, no off-flavors, and specific positive emotional responses for the pecan kernels. There are only four publications associated with consumer acceptance of pecan kernel or related pecan products [ 6 , 7 , 8 , 9 ], and overall acceptance is commonly included in these studies. However, no studies have focused on the driven factors for the overall acceptance of pecan kernels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations